2023
DOI: 10.1128/jvi.01612-22
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin Receptor Protein 1 Is an Entry Factor for Rabies Virus

Abstract: For most viruses, cell entry involves engagement with many distinct plasma membrane components, each of which is essential. After binding to its specific receptor(s), rabies virus (RABV) enters host cells through the process of clathrin-mediated endocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Our previous studies ( 26 ) combined with the above results demonstrate that TfR1, mGluR2, and RABV G interact with each other, which suggests that they might form a complex. To test this hypothesis, we performed a protein interaction competition assay.…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…Our previous studies ( 26 ) combined with the above results demonstrate that TfR1, mGluR2, and RABV G interact with each other, which suggests that they might form a complex. To test this hypothesis, we performed a protein interaction competition assay.…”
Section: Resultssupporting
confidence: 56%
“…Interestingly, the lifetime of RABV endocytosis is also longer than that of classic TfR1 endocytosis ( 19 , 33 , 34 ). More importantly, in a recent study, we demonstrate that TfR1 is an entry factor for RABV ( 26 ). Therefore, we performed a co-immunoprecipitation assay using Flag-tagged mGluR2 protein (mGluR2-Flag) and Myc-tagged TfR1 protein (TfR1-Myc) in plasmid-transfected HEK293 cells to validate the interaction.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…Despite the advancement in rabies research which identified multiple cellular receptors for RABV (1,6-10), none of the previous studies have identified any of these receptors as indispensable for virus entry. To date, six cellular receptors have been identified to facilitate RABV entry such as nicotinic acetylcholine receptor α1 (nAChRα1) (11), neural cell adhesion molecule, (NCAM) (9), metabotropic glutamate receptor 2 (mGluR2) (7), integrin beta 1 (ITGB1) (1) and transferrin receptor protein 1 (10).…”
Section: Introductionmentioning
confidence: 99%